Cephalometric evaluation of the modified maxillary protraction face mask - Al Takı, Amjad Ahmad (My University, 2002)
Bu araştırmanın amacı, yeni modifiye edilmiş bir maksiller protraksiyon yüz maskesinin etkilerini incelemekti. Bu çalışmaya 12 hasta(7 kız 5 erkek) dahil edildi; hastalar Marmara Üniversitesi dişhekimliği fakültesi ortodonti bölümü kliniğine gelenler arasından seçildi.Kız hastaların yaşları 8.33 ile 13.66 arasında ortalama 12.14 idi. Erkek hastaların yaşları 11.83 ile 13.58 rasında ortalama 12.80 idi. Çalışma grubunun yaş ortalaması 12.42 idi. Tüm hastalar retrognatik maksilla ve ortognatik mandibulaya sahip iskeletsel Sınıf III bireylerdi. Her hasta için akrilik cap splintli full coverage hyrax genişletme vidası hazırlandı ve 7 gün boyunca hızlı palatal genişletme yapıldı.7nci günde, özel olarak tasarlanmış yüz arkı ve Petit tip yüz maskesi ile protraksiyon tedavisi başlatıldı. Yüz arkı, kuvvetin uygulanma noktasını maksillanın direnç merkezinden geçirmek üzere yükseltmek ve her iki tarafta da paralel elastik kuvvet uygulamak için yukarı doğru büküldü. Tek taraflı 500 gm kuvvet uygulandı ve hastalar yüz maskesini 16saat/ gün giymek üzere yönlendirildiler. Tedavi ortalama 7.5 ay sürdü. Yüz maskesinin uygulanmasından önce ve çıkarılmasından ve akrilik cap splintin uzaklaştırılmasından hemen sonra lateral sefalometrik filmler alındı. Aşağıdaki sonuçlar bulundu: 1.Uygulama A noktasını öne doğru 2.41 mm hareket ettirerek başarılı oldu. 2.Maksillanın saat yönünün tersine rotasyon olmaksızın öne translasyonu sağlandı. 3.Maksiller oklüzal düzlem saat yönünde belirgin rotasyon gösterdi. 4.Maksiller dişlerin saat yönünde rotasyonu nedeniyle maksiller dişler uzadı ve geriye doğru yattı. 5.Hem maksillanın öne doğru uzamasına, hem de yüz maskesinin chin cup etkisine bağlı olarak, mandibula aşağı ve geriye doğru yer değiştirdi. Sonuç olarak, Nanda'nın 1980'de tanıttığı yüz arkından modifiye ettiğimiz yeni yüz arkımızla, maksillayı gövdesel olarak öne aldık ve aynı zamanda tüm protraktiv kuvvetlerin maksillayı öne almak için kullanıldığı daha etkili bir kuvvet sistemine sahip olduk ki, daha önceki yüz maskesi tasarımında protraktiv kuvvetin sadece bir kısmı maksillayı öne almakta kulanılabiliyordu ve daha az etkili bir kuvvet sistemi vardı. CEPHALOMETRIC EVALUATION OF THE MODIFIED MAXILLARY PROTRACTION FACE MASK

The aim of this study was to examine the effects of the newly modified maxillary protraction face mask. This study included 12 patients (7 females and 5 males); they were selected from the clinical intake of the orthodontic department in the dental faculty of Marmara University. The age of the female patients ranged from 8.33 to 13.66 years with an average of 12.14 ± 1.96 years. The age of the male patients ranged from 11.83 to 13.58 years with an average of 12.80 ± 0.74 years. Mean age for the study group was 12.42 ± 1.66 years. All patients were Class III skeletally with retrognathic maxilla and orthognathic mandible. For each patient, hyrax expansion screw with a full coverage acrylic cap splint was constructed and rapid palatal expansion was performed for 7 days. At the 7th day, protraction therapy with the combination of a specially designed face bow and Petit type face mask was started. The face bow was bent upward to raise point of force application to pass through the center of resistance of the maxilla, and to have parallel application of the elastic force in both sides. A unilateral 500 gm force was applied and the patients were instructed to wear the face mask for 16 h/ day. The average treatment time was 7.5 months. Lateral cephalometric films were taken before and immediately after discontinuation of face mask and removal of the acrylic cap splint. The following results were obtained: 1.The appliance was effective in protracting the maxilla where point A moved anteriorly by 2.41 mm. 2.Anterior translation of the maxilla without counterclockwise rotation was achieved. 3.Maxillary occlusal plane showed a significant clockwise rotation. 4.Maxillary incisors were extruded and retroclined because of the clockwise rotation of maxillary dentition. 5.The mandible was displaced downward and backward due to both anterior elongation of the maxilla and the chin cup effect of the face mask. In conclusion, by introducing our new face bow design, which was modified from the one introduced by Nanda in 1980, we were able to protract the maxilla bodily and at the same time to have a more effective force system where the whole given protractive force was utilized in protracting the maxilla, while in the previous face bow design only part of the protractive force was utilized in maxillary protraction and thus had less effective force system.
Keywords: Ortodonti